Decentralized supply chain network design: Monopoly, duopoly and oligopoly competitions under uncertainty - Seyed Mohammad Seyedhosseini; Kaveh Fahimi; Ahmad Makui (Journal of Industrial Engineering International, 2018)
This paper presents the competitive supply chain network design problem in which n decentralized supply chains simultaneously enter the market with no existing rival chain, shape their networks and set wholesale and retail prices in competitive mode. The customer demand is elastic and price dependent, customer utility function is based on the Hoteling model and the chains produce identical or highly substitutable products. We construct a solution algorithm based on bi-level programming and possibility theory. In the proposed bi-level model, the inner part sets the prices based on simultaneous extra- and Stackleberg intra- chains competitions, and the outer part shapes the networks in cooperative competitions. Finally, we use a real-word study to discuss the effect of the different structures of the competitors on the equilibrium solution. Moreover, sensitivity analyses are conducted and managerial insights are offered.
Keywords: 650; Competitive decentralized supply chain network design; Nash equilibrium; Fuzzy multi-level programing; Bi-level programing